Combined antibacterial effects of tissue‐tolerable plasma and a modern conventional liquid antiseptic on chronic wound treatment. Issue 5 (21st March 2014) - Klebes, Martin; Ulrich, Christin; Kluschke, Franziska; Patzelt, Alexa; Vandersee, Staffan; Richter, Heike; Bob, Adrienne; von Hutten, Johanna; Krediet, Jorien T.; Kramer, Axel; Lademann, Jürgen; Lange‐Asschenfeld, Bernhard
<x xml:space="preserve">Abstract</x> Potential antimicrobial effects of sequential applications of tissue‐tolerable plasma (TTP) and the conventional liquid antiseptic octenidine dihydrochloride (ODC) were investigated. 34 patients with chronic leg ulcers were treated with TTP, ODC or a combination of both. The bacterial colonization was measured semi‐quantitatively before and immediately after treatment and changes in the microbial strains' compositions before and after antiseptic treatments were analyzed. All antiseptic procedures reduced the bacterial counts significantly. The sequential application of TTP and ODC displayed the highest antimicrobial efficacy. Me combined use of TTP and conventional antiseptics might represent the most efficient strategy for antiseptic treatment of chronic wounds. (© 2014 WILEY‐VCH Verlag GmbH &Co. KGaA, Weinheim)